Ginseng ameliorates exercise-induced fatigue potentially by regulating the gut microbiota. Issue 9 (6th April 2021) - Zhou, Shan-Shan; Zhou, Jing; Xu, Jin-Di; Shen, Hong; Kong, Ming; Yip, Ka-Man; Han, Quan-Bin; Zhao, Zhong-Zhen; Xu, Jun; Chen, Hu-Biao; Li, Song-Lin
Abstract : WEG showed strong anti-EF effects by the beneficial effects of saccharides and ginsenosides on gut microbiota, then energy metabolism abnormality, lipid peroxidation and metabolic disorder as well as inflammatory response. Abstract : The therapeutic effects of water extract of ginseng (WEG) on exercise-induced fatigue (EF) have been reported in several previous studies, but the molecular mechanisms involved remain unexplored. In this study, the anti-EF effects of WEG were studied, and the potential mechanisms were discussed. We characterized the chemical components of WEG by ultra-high performance liquid chromatography-tandem triple quadrupole mass spectrometry (UHPLC-QqQ-MS/MS) and high performance liquid chromatography coupled with evaporative light scattering detection (HPLC-ELSD), and then examined the anti-EF effects of WEG on a rat model of weight-loaded swimming with a focus on endogenous metabolism and gut microbiota. WEG contains abundant (90.15%, w/w) saccharides and ginsenosides with structurally diverse glycosyls. WEG taken orally showed strong anti-EF effects by ameliorating energy metabolism abnormality, oxidative stress, lipid peroxidation, inflammatory response, disorders in the metabolism of bile acid, amino acid, fatty acid and lipid, as well as the gut microbiota dysbiosis. Given that gut microbiota is significantly associated with energy expenditure, systemic inflammation and host metabolism, these findings suggest a potential central role of the gut microbiota in mediating the anti-EF effect of WEG. That is, the saccharides and ginsenosides in WEG serve as energy substrates for specific intestinal bacteria, thereby beneficially regulating the gut microbiota, and the reshaped gut microbial ecosystem then triggers several molecular and cellular signaling pathways ( e.g. butyrate or TGR5 signals) to achieve the therapeutic effects on EF. The outcomes highlighted here enable deeper insight into how WEG overcomes EF.